Robot-assisted thoracoscopic surgery vs. sternotomy for thymectomy: A systematic review and meta-analysis - Wang, Cheng-qian; Wang, Jie; Liu, Fei-yu; Wang, Wei (Frontiers in Surgery, 2023)
Abstract Introduction: Surgeons have widely regarded sternotomy (ST) as the standard surgical method for thymectomy. Minimally invasive methods for thymectomy, including video-assisted and robot-assisted thoracoscopic surgery (RATS), have been explored. There are some studies have researched and compared the outcomes of patients after robotic and sternotomy procedure. Methods: We searched the databases of Pubmed, the Cochrane Library, Embase and selected the studies on the efficacy and safety of RATS or ST for thymectomy. Meta-analysis was performed for operation time, operation blood loss, postoperative drainage time, operative complications and hospitalization time. Results: A total of 16[2, 6-20] cohort studies with 1089 patients were included. Compared to ST, RATS is an appropriate alternative for thymectomy which reduced operation blood loss [standardized mean difference (SMD) = -1.82, 95% confidence interval (95% CI): (-2.64,-0.99), p = 0.000], postoperative drainage time [SMD = -2.47, 95% Cl: (-3.45,-1.48), p = 0.000], operative complications [odds ratio (OR) = 0.31, 95% Cl: (0.18,0.51), p = 0.000] and hospitalization time [SMD = -1.62, 95% Cl: (-2.16,-1.07), p = 0.000]. Conclusions: This meta-analysis based on cohort studies shows that RATS has more advantages over ST. Therefore, RATS is a more advanced and suitable surgical method for thymectomy. Keywords: Robot-assisted thoracoscopic surgery, sternotomy, thymectomy, systematic review, meta-analysis.